Vgll2a is required for neural crest cell survival during zebrafish craniofacial development - Johnson, Christopher W. (2011)
Invertebrate and vertebrate vestigial (vg) and vestigial-like (vgl) genes are involved in embryonic patterning and cell fate determination. These genes encode cofactors that interact with members of the TEAD/Scalloped family of transcription factors and modulate their activity. We have previously shown that, in mice, Vgll2 is differentially expressed in the developing facial prominences. In this study, we show that the zebrafish ortholog vgll2a is expressed in the pharyngeal endoderm and ectoderm surrounding the neural crest derived mesenchyme of the pharyngeal arches. Moreover, both the FGF and retinoic acid (RA) signaling pathways, which are critical components of the hierarchy controlling craniofacial patterning, regulate this domain of vgll2a expression. Consistent with these observations, vgll2a is required within the pharyngeal endoderm for NCC survival and pharyngeal cartilage development. Specifically, knockdown of Vgll2a in zebrafish embryos using Morpholino injection results in increased cell death within the pharyngeal arches, aberrant endodermal pouch morphogenesis, and hypoplastic cranial cartilages. Overall, our data reveal a novel non-cell autonomous role for Vgll2a in development of the NCC-derived vertebrate craniofacial skeleton.